Avaliação da implementação do PROEJA em municípios do Oeste do Paraná (2008-2009). - Hotz, Karina Griggio (2010)
This work is concerned to the study of the National Program of Professional Education Integration with the Basic Education in the Young Persons and Adults Education Modality (PROEJA) created by the Ministry of Education (MEC). Our objective is to evaluate the implementation process of the Program in the state public net of local municipalities of the West of the Paraná: Cascavel, Foz do Iguaçu and Medianeira, in the first two years it was offered the PROEJA courses in the State, respectively, the years 2008 and 2009, it has been done trying to check how the implementation process has been achieved the objectives proposed in the main documents and what difficulties it has been found in the implementation process. Focusing on the accomplishment of our objective, we try, in the first chapter, to understand the PROEJA determinants. Considering that the effectiveness of a social politic and, therefore educational, has it origin in the productive structure and in the class struggles, we intended, in this chapter, to understand the context of the productive restructures and the Basic Education reform. In the second chapter, we characterize the PROEJA education politic, considering the recent history of the Brazilian education politics for the high school education and for the Education of Young persons and Adults, intending to understand the context that preceded the PROEJA which made possible its foundation in the country and in the Paraná state. We will discuss also about the legality, pedagogic, administrative and financial aspects and the functions of the PROEJA, as well as its articulation to the demands of the productive restructuring, expressed in a particular way by State claims and by the international organisms. In the third chapter we aimed to characterize economically and socially of the municipalities researched with the intention of bringing elements that helped in the evaluation of the implementation of the PROEJA in the public schools of these towns. In the four chapter we present data and informations constituted, fundamentally, based in the research project Demands and potentialities of the PROEJA in the Paraná State . The researches of this work are from the Technological Federal University of the Paraná (UTFPR), Federal University of the Paraná (UFPR) and State University of the West of the Paraná (UNIOESTE), is based from the experience lived in the extension project Demands and Potentialities of the PROEJA in the Paraná State: a contribution to the continued formation of professionals connected to the PROEJA courses in the Western Region of the Paraná performed by UNIOESTE researchers and based on data collected at the State Secretary of Education of the Paraná (SEED). In the fifth and last chapter, based on the knowledge built in the previous chapters, we try to discuss in a objective way about the research, evaluating the PROEJA implementation at municipalities of the West of the State. In the final considerations we made a more general analysis on the evaluation performed in the last chapter intending to understand if the PROEJA objectives can be reached in the towns of the West of the Paraná by the way it has been implemented, what wide determinants that defined its offer in Brazil, in the Paraná State and in the towns studied and what are the political and ideological objectives that it is intended to reach with the Program.